EFFECTS OF SURAH AR-RAHMAN THERAPY ON THE ANXIETY LEVELS OF MEDICAL STUDENTS - Nayab Ali; Saba Afzal; Muhammad Arham Abbas; Hadia Mohsin; Rabia Mahmood; Muhammad Rehan (International Journal of Islamic and Complementary Medicine, 2025)
Anxiety disorders have significantly deteriorated the mental well-being of our young populace, especially medical students, due to the demanding academic curriculum, rigorous study schedules, and the burden of expectations to excel as proficient professionals. Various methods to alleviate anxiety have been employed previously, among which Quran therapy has demonstrated remarkable efficacy for Muslims. The objective of this study is to assess the impact of Surah al-Rahman therapy (the 55th chapter of the Holy Quran) on anxiety levels among 2nd year medical students. A pre-post experimental study was carried out on a sample of 68 participants from the 2nd year of MBBS at Federal Medical College. The participants were classified into two categories: Category 1 encompassed individuals who underwent 1-6 sessions, while Category 2 comprised those who underwent 7-12 sessions. Anxiety levels were evaluated utilizing the Beck Anxiety Inventory (BAI). Data analysis was conducted using SPSS version 25, incorporating descriptive statistics and tests for median difference. The findings of the study indicate that the proportion of participants experiencing severe anxiety decreased from 24.6% (pre-therapy) to 3.1% (post-therapy). Positive outcomes in anxiety reduction were observed irrespective of gender and residency location (p-value >0.005). A significant difference in anxiety scores between pre-therapy and post-therapy was noted in both categories. The conclusion of the study imply that Surah-Ar-Rahman therapy is an effective technique in alleviating anxiety. If sessions of Surah-Ar-Rahman therapy are regularly organized in medical institutions, the spiritual development of medical students could be substantially enhanced, fostering self-assurance and competence essential for excelling in their medical careers. Study limitations: small sample size and no control group.   ABSTRAK Gangguan kecemasan telah secara signifikan memperburuk kesehatan mental populasi muda kita, terutama mahasiswa kedokteran, karena kurikulum akademik yang menuntut, jadwal belajar yang ketat, dan beban ekspektasi untuk menjadi profesional yang mahir. Berbagai metode untuk meringankan kecemasan telah digunakan sebelumnya, di antaranya terapi Al-Quran yang telah menunjukkan kemanjuran yang luar biasa bagi umat Islam. Tujuan dari penelitian ini adalah untuk menilai dampak dari terapi Surah al-Rahman (surah ke-55 dalam Al-Quran) terhadap tingkat kecemasan di kalangan mahasiswa kedokteran tahun kedua. Sebuah studi eksperimental pra-pasca dilakukan pada sampel 68 peserta dari tahun ke-2 MBBS di Federal Medical College. Para peserta diklasifikasikan ke dalam dua kategori: Kategori 1 mencakup individu yang menjalani 1-6 sesi, sedangkan Kategori 2 terdiri dari mereka yang menjalani 7-12 sesi. Tingkat kecemasan dievaluasi dengan menggunakan Beck Anxiety Inventory (BAI). Analisis data dilakukan dengan menggunakan SPSS versi 25, dengan menggunakan statistik deskriptif dan uji perbedaan median. Temuan dari penelitian ini menunjukkan bahwa proporsi peserta yang mengalami kecemasan berat menurun dari 24,6% (sebelum terapi) menjadi 3,1% (setelah terapi). Hasil positif dalam pengurangan kecemasan diamati terlepas dari jenis kelamin dan lokasi tempat tinggal (p-value>0,005). Perbedaan yang signifikan dalam skor kecemasan antara pra-terapi dan pasca-terapi dicatat pada kedua kategori. Kesimpulan dari penelitian ini menyiratkan bahwa terapi Surah Ar-Rahman adalah teknik yang efektif dalam mengurangi kecemasan. Jika sesi terapi Surah-Ar-Rahman diselenggarakan secara teratur di institusi medis, perkembangan spiritual mahasiswa kedokteran dapat ditingkatkan secara substansial, menumbuhkan kepercayaan diri dan kompetensi yang penting untuk unggul dalam karir medis mereka. Keterbatasan penelitian: jumlah sampel yang kecil dan tidak ada kelompok kontrol.